EFFORT TO INCREASE THROUGH LEARNING OUTCOMES LONG JUMP ORTODOCKS STYLE WITH DEMONSTRATION METHOD OF CLASS VIII JUNIOR HIGH SCHOOL BAKTI FIELD PRIVATE CHARITY 2016 ACADEMIC YEAR - WINATA, DEVI CATUR (ACPES 2017, 2017)
This study aims to find out how to improve learning outcomes Long Jump Ortodock StyleThrough Demonstration Method on VIII students of Private Junior High School Amal Bakti Medanacademic year 2016. The time of the research was conducted in August 2016. The object of thisresearch is the students of class VIII with the number of students 25 people consisting of 12 malestudents and 13 female students who will be given the action in the form of learning variation onthe learning results of Long Jump.Based on the results of student learning in the first cycle of the test results of learning I can beseen that the initial ability of students in doing the technique long jump is still low. Of the 25students there are 15 people (60%) who have achieved mastery learning, while 10 people (40%)have not reached mastery learning. With the average value of student learning outcomes is 76.3.While in the second cycle can be seen that the ability of students in performing the test results oflearning have been increasing klasikal. Of the 25 students there are 22 people (88%) who haveachieved learning mastery, while 3 people (13%) have not reached mastery learning. With theaverage value of student learning outcomes is 80.7, so there is a 25% increase in learningoutcomes from cycle I to cycle II .Based on that it can be concluded that the learning through variation of Learning can improvethe results of Long Jump Ortodock Style in VIII students of Private Junior High School Amal BaktiMedan Academic Year 2016